(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In beginning Islam did not materially influence Indian Art. The Muslims were in small numbers and there were very few craftsman among them. Before the advent of the Mughals there was little progress in Art. At the outset the Mughal domination was marked by a fresh wave of pure Iranianism, as well as by the coming of ottoman influence. Babur was very busy in wars so they didn’t have much time to build. We owe him scarcely anything but the mosque of Panipat and Jama Masjid at Sambhal. Under the reign of Akbar, Yusuf, built the palaces of Delhi, Agra and Lahore. During Jahangir period, in architecture his age is a period of transition between the splendour and practical Nature of Akbar’s buildings. Under Shahjahan Mughal architecture reached its peak point. The style of his reign is characterized by a new wave of Persian inspiration, but we should always bear in mind that the buildings which he constructed are distinguished from the Constantinople by the use of white marble circular domes, High minarets, Mehrab, various types of pillars, big doorways and large compounds, forts, royal-palaces, fountains, baths Diwan-i-khas, Diwan-i-aam and Mosques were given special care Till Jahangir’s regime, Redstone was mainly used in buildings while white marble was also used at certain places. However, marble was largely used during the regime of Shah Jahan. The buildings during the Mughal period were adorned with precious stones, diamonds and jewels. Walls and ceilings were engraved with several types of designs of flowers and paintings.In about the year 1200 the whole of northern India came under Muslim rule and Delhi became the capital. The previous architectural patterns of the Hindus were rich in sculpture and decorations, often having representation of human and animals, but Islam prohibited the representation of living beings, and so the builders had to invent devices to make it more attractive. The Mughal period was the most creative one and new ideas were introduced. Under the Mughals, this simplification was to lead to a harmonious fusion of Jain and Persian art and to the birth of a new art which was of a genuinely original and classic nature. Mughal architecture falls into two broad divisions Mosques and tombs are types of religious monument, and others are the secular kind, like palaces, fortresses and city gates.